Cranial ultrasound evaluation in term neonates. (April 2020) - Luciano, R.; Bersani, I.; Mancini, G.; Vento, G.; Mercuri, E.
Abstract: Background: Term neonates (TN) are not routinely submitted to cranial ultrasound scan (CUS), since they are not considered at high risk for developing cerebral lesions. Aims: To investigate the prevalence of cerebral abnormal findings in term neonates (TN), to identify the associated clinical features and to better target neonatal CUS investigations. Study design: Prospective observational study. Subjects: A total number of 1805 healthy TN underwent CUS. 1181 neonates had clinical features supposed to increase the risk for cerebral abnormal findings (study cohort), 624 were controls. Outcome measures: Prevalence of minimal, minor, and major cerebral abnormal findings was analyzed in six different categories of low-risk TN and compared to controls. Results: Variations from normality at the neonatal CUS were observed in 402 TN (22.27%). In half of the cases the ultrasound findings were minimal abnormal findings, while minor abnormal findings were found in 179 TN (9.92%). About 1% of the studied neonates showed major cerebral abnormal findings potentially compromising neurodevelopmental outcome. The prevalence of the observed abnormal findings varied significantly in the different low-risk categories. Conclusions: The clinical features significantly increasing the risk for cerebral anomalies in healthy TN were microcrania, macrocrania, mild neurologic signs, and the detection of mild variations from normal cerebral aspect at the antenatal ultrasound evaluation. Highlights: There is no indication for routine head ultrasound screening in healthy TN. The aim of the study is to better target CUS investigation in healthy TN. We identify a few clinical features increasing the risk for CUS abnormalities in TN.